Oikos: Reintegrating nature and civilization (Revista LABVERDE, 2011)
Incorporate ecological principles to all human activity requires changes in the economic model, still based on outdated paradigms, requires changes in the mode of production that now consumes resources and pollutes too much, and also requires a profound transformation in the culture of values that persist in a consumerist inconsequential model. The process of formation and transformation of the city is strongly influenced by these factors. The precariousness of the city and its impact on the environment reveal the historical distance between the market and mechanistic logic and natural laws that govern the functioning of ecosystems. We need a harmonious reintegration between human activities and processes that govern the functioning of ecosystems. This reintegration must seek expression in the design of our cities and buildings.